2012
DOI: 10.1111/j.1471-0528.2012.03280.x
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between colposcopic impression and histological diagnosis among human papillomavirus type 16‐positive women: a clinical trial using dynamic spectral imaging colposcopy

Abstract: Objective To investigate the agreement between conventional colposcopic impression, dynamic spectral imaging (DSI) colposcopy and histology, for human papillomavirus type 16-positive (HPV16 + ) and non-16 high-risk (hr) HPV + women.Design Prospective, comparative, multicentre clinical trial.Setting Three colposcopy clinics in the Netherlands.Population Women (n = 177) aged 18 years or over with an intact cervix, referred for colposcopy.Methods The colposcopist graded the lesion by using the DSI colposcope as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 22 publications
2
38
1
1
Order By: Relevance
“…However, the sensitivity of dynamic spectral imaging colposcopy for CIN2+ was higher in HPV16-positive than in non-16 hrHPV-positive women which may be explained by the better identification of small CIN2 lesions with this technique. 22 This is in agreement with our finding that in this population of women with abnormal cervical screening results, the visual colposcopic appearance of HPV16-positive women does not differ from that in women infected with other HPV types. Studies have shown that HPV16 is the genotype with the highest oncogenic potential because it is associated with the highest risk of the development of CIN3 and cancer and has the highest worldwide attribution for CIN2+ and ICC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the sensitivity of dynamic spectral imaging colposcopy for CIN2+ was higher in HPV16-positive than in non-16 hrHPV-positive women which may be explained by the better identification of small CIN2 lesions with this technique. 22 This is in agreement with our finding that in this population of women with abnormal cervical screening results, the visual colposcopic appearance of HPV16-positive women does not differ from that in women infected with other HPV types. Studies have shown that HPV16 is the genotype with the highest oncogenic potential because it is associated with the highest risk of the development of CIN3 and cancer and has the highest worldwide attribution for CIN2+ and ICC.…”
Section: Discussionsupporting
confidence: 92%
“…Our theory is in line with the findings of Wentzensen et al, 31 who observed a difference in lesion size between women with HPV16 and other types in CIN2, but not in CIN3. Zaal et al 22 found that with conventional visual colposcopy, no difference in sensitivity for CIN2+ lesions caused by different HPV types was found. However, the sensitivity of dynamic spectral imaging colposcopy for CIN2+ was higher in HPV16-positive than in non-16 hrHPV-positive women which may be explained by the better identification of small CIN2 lesions with this technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this was not the aim of the study and these results are not reliable enough, the sensitivity of DySIS was similar to that found in previously published clinical trials [14,15,16]. …”
Section: Discussionmentioning
confidence: 50%
“…It is a digital colposcope that can be used to perform CC and also measures the dynamic color changes associated with cervical lesions after the application of acetic acid. During the examination, the software that is embedded in the device calculates and displays a color-coded map that represents not only the localization, but also reflects the severity of the cervical lesion, indicating the best areas for biopsies [15,16]. It has been demonstrated that when the DySIS map is integrated in the colposcopic examination, the colposcopic sensitivity to detect high-grade disease increases significantly [15].…”
Section: Introductionmentioning
confidence: 99%